Anais Do I Congresso Brasileiro De Biotecnologia on-Line 2021
DOI: 10.51189/rema/799
|View full text |Cite
|
Sign up to set email alerts
|

TESTE DA ATIVIDADE ANTIMICROBIANA DO ÓLEO ESSENCIAL DO TOMILHO (Thymus vulgaris)

Abstract: Introdução: O tomilho (Thymus vulgaris L.) é uma planta da família Lamiaceae que compreende cerca de 350 espécies. Muitas das espécies introduzidas no Brasil são plantas medicinais, aromáticas e produtoras de óleos essenciais. Objetivo: Este trabalho tem como objetivo revisar a eficácia do óleo essencial de tomilho na atividade antimicrobiana. Material e métodos: Foram selecionados do site Scopus 7 artigos científicos sobre o tema em estudo com as palavras chaves: Thymus vulgaris, essential oil e anti microbia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…In a study previously carried out by Jakiemiu et al, (2010) the compounds in larger amounts found were thymol (54 to 57%), p-cymene (12 to 15%) and y-terpinene (6 to 7%). Romero et al, (2009) also found similar results, with thymol (50%), p-cymene (20%) and y-terpinene (18%) as the majority compounds. Although the studies cited show different results as to the percentage of oil constituents, it can be observed in all that the compound in larger quantities of the thyme EO was thymol.…”
Section: Resultssupporting
confidence: 69%
“…In a study previously carried out by Jakiemiu et al, (2010) the compounds in larger amounts found were thymol (54 to 57%), p-cymene (12 to 15%) and y-terpinene (6 to 7%). Romero et al, (2009) also found similar results, with thymol (50%), p-cymene (20%) and y-terpinene (18%) as the majority compounds. Although the studies cited show different results as to the percentage of oil constituents, it can be observed in all that the compound in larger quantities of the thyme EO was thymol.…”
Section: Resultssupporting
confidence: 69%